An estimation of the nominal exchange rate level that would eliminate the mexican currency misalignment: is it moving in the right direction in 2025? Una estimación del tipo de cambio nominal que eliminaría del desalineamiento cambiario del peso mexicano: ¿se está moviendo en la dirección correcta en 2025? - Jiménez Gómez, Adrián; Flores Márquez, Héctor; Absalón Copete, Carlos (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
We estimate an approximation of the equilibrium real exchange rate to measure the Mexican currency overvaluation, which is approximately of 25.3% in the first quarter of 2024. The nominal exchange rate level that would return the real exchange rate to its equilibrium level would be 22.77 Mexican pesos per US dollar, in contrast to an average nominal exchange rate of 17.00 observed in first quarter of 2024 and an average nominal exchange rate of 19.51 in the second quarter of 2025. The National Institute of Statistics and Geography (INEGI) changed in 2023 the base year to measure real variables as GDP, private consumption, public consumption and exports from 2013 to 2018 chained pesos. It is essential to estimate the VAR and a VEC models for period 1995Q1-2024Q1 using the new time series provided by INEGI to obtain updated and subsequent estimates of the magnitude and how it changes the Mexican peso overvaluation. The fitted values of the cointegration equation provide us with the approximation of the equilibrium real exchange rate. Although the observed real exchange rate has risen from the local minimum reached in the first quarter of 2024, it is appreciating again starting in the second quarter of 2025. If this appreciation continues, there is a risk of a return to significant exchange rate overvaluation.